2021
DOI: 10.1371/journal.pone.0245076
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy study: Short-term application of radiofrequency ablation and stereotactic body radiotherapy for Barcelona Clinical Liver Cancer stage 0–B1 hepatocellular carcinoma

Abstract: Aim To evaluate the safety and efficacy of the administration of radiofrequency ablation (RFA) and stereotactic body radiotherapy (SBRT) in the short term to the same patients in Barcelona Clinical Liver Cancer (BCLC) stages 0–B1. Methods From April 2014 to June 2019, we retrospectively reviewed BCLC stage 0–B1 patients with fresh hepatocellular carcinoma (HCC) lesions that were repeatedly treated by RFA (control group, n = 72), and by RFA and subsequent SBRT (case group, n = 26). Propensity score matching (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As the technique of radiotherapy evolves, the role of radiotherapy in the treatment of hepatocellular cancer has been explored. Previous studies have demonstrated the safety of SBRT plus ablation in early and even intermediate‐stage HCC 13 15 , therefore, we analyzed data from the publicly accessible SEER database to compare the efficacy of radiotherapy plus ablation and ablation alone in early-stage HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the technique of radiotherapy evolves, the role of radiotherapy in the treatment of hepatocellular cancer has been explored. Previous studies have demonstrated the safety of SBRT plus ablation in early and even intermediate‐stage HCC 13 15 , therefore, we analyzed data from the publicly accessible SEER database to compare the efficacy of radiotherapy plus ablation and ablation alone in early-stage HCC.…”
Section: Discussionmentioning
confidence: 99%
“…5 A). However, a retrospective study reported that the safety and efficacy of SBRT plus ablation were similar to ablation alone in HCC patients at the stage of 0-B1 13 , therefore, we speculated that “beam radiation” may include other kinds of radiation therapy whose efficacy are worse than SBRT. Moreover, we needed to cleared that part of patients treated with combination therapy might use radiotherapy as a salvage treatment which might lead to selection bias in the population between two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation